Duties and Functions of Immigration Attache and Immigration Technical Staff - Asto Yudho Kartiko; Anita Herlina (Journal of Law and Border Protection, 2019)
The era of Globalization has a possibility for us as a human an easy way and flexibility almost in every kind of sections. It is also made things easier for us in benefit of technology advance in every sections. After that, one of our convenience is that we could stay or live in another country. When it comes to live in another country we as a foreigner is far from reach of our homeland, in other words we’re not under our homeland protection no more. Therefore, there’s Embassy as a representation of a foreign country in another nation. Besides, Embassy also needs an expert on every sections. Because of that, it is need an officials that have an expert on specific sections that called Embassy Attaché. One of those sections that has an officials or Embassy Attaché is Immigration’s section. Immigration section’s Attaché had a spesifical task and function simply and solely is on Immigration things such a passport services, self reporting, also Official Passports renewal.